The Accountant Position in the Context of State Governance in Indonesia - Hidayatullah; Asril, Ardison (Indonesian Journal of Contemporary Multidisciplinary Research, 2025)
This study examines the strategic position of accountants within the context of state governance in Indonesia, particularly in supporting transparency, accountability, and good governance. Accountants in the public sector play a crucial role in managing state finances, including planning, recording, reporting, and overseeing financial activities in accordance with good governance principles. A juridical-normative approach is used to analyze relevant regulations, ranging from laws to regional accounting policies. The findings indicate that accountants make a significant contribution to fostering transparent governance, although challenges remain, such as policy harmonization and professional capacity building. This study recommends strengthening regulations, enhancing policy synergy, and improving professional accounting education to support sustainable bureaucratic reform.